SEDIMENT TRAPPING BY TERRACED PADDY FIELD ON SLOPPING AGRICULTURAL LAND - Sukristiyonubowo Sukristiyonubowo; D. Gabriels; M. Verlooc (Indonesian Agency for Agricultural Research and Development, 2010)
Terraced paddy field is not only important for rural food security, but also for trapping sediment in the slopping land. The aims of this research were to quantify the amount of incoming and outgoing sediments and to study sediment movement behavior during harrowing and fertilizing under traditional irrigation of terraced paddy field system. This study was carried out at Keji Village, Semarang District, Central Java during two cropping seasons, a wet season 2003/04 and a dry season 2004. A paddy field with eight terraces was selected. The terraces were flat, different in size and descending to the river. Sediment samples were taken at harrowing and fertilizing activities. The results indicated that at harrowing, outgoing sediment was higher than incoming both during the wet and the dry seasons. About 0.53 and 0.27 t ha-1 day-1 of soil were eroded during harrowing in the wet and the dry seasons, respectively. However, a week before and after fertilizing, both in the wet and the dry seasons, the amounts of incoming sediment were higher than the outgoing one. In the wet season, the amounts of incoming sediments were three to four times higher than the outgoing one, both a week before and after fertilizing. During the wet season, about 0.31 and 0.34 t ha-1 day-1 of sediment was yielded a week before and after fertilizing, respectively. During the dry season, the incoming sediments were ten times higher than the outgoing one. On an average the sediment yields were about 0.07 and 0.08 t ha-1 day-1 a week before and after fertilizing, respectively. Terraces having greater areas deposited more sediment than those with smaller sizes. During a week before and after first fertilizing, the total amounts of incoming sediments were 6.44 and 1.19 t ha-1 for the wet and dry seasons, while that of outgoing sediments were 1.89 and 0.14 t ha-1 for the wet and dry seasons, respectively. This indicates that terraced paddy fields are not only producing rice, but also providing environmental service in term of sediment trapping. This external service minimizes sedimentation in the downstream.